Optimizing Community Potential in Religion and Culture-Based Tourism Communication in Langkat Regency - Mahardhika Sastra Nasution; Hasan Sazali; Irma Yusriani Simamora (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
The development of religion and culture-based tourism in Langkat Regency positions the community as the primary actor in creating authentic tourism experiences. The attractiveness of a destination is determined not only by its natural or cultural heritage, but also by the quality of interactions between tourists and local residents. This study aims to describe the development of community potential, forms of tourism communication, and the image and optimization of the community's role in religion- and culture-based tourism in Langkat. The study used a qualitative descriptive method through the collection of field data and related literature. The results indicate that local communities play a significant role as the primary drivers in destination development, particularly in religious tourism areas. The developing tourism communication pattern remains traditional through informal channels, primarily word-of-mouth. In the Besilam region, the dissemination of tourism information relies heavily on the social networks of religious orders, religious leaders, and the local community. To optimize community potential sustainably, strategic collaboration is necessary between the local government, religious leaders, tourism managers, and the community. This synergy is crucial for building tourism governance that not only boosts the economy but also preserves local religious and cultural values.